Repercussion of a perceptive-motor training program on the efficacy in competition from handball female goalkeeper according to the shot type - Antonio Antúnez Medina; María-; Francisco Manuel Argudo Iturriaga; Encarnación Ruiz Lara; José Luis Arias Estero (Federación Extremeña de Balonmano; University of Extremadura, 2010)
Abstract This study aimed to analyze the application of a perceptive-motor training program effect in the handball goalkeeper and value the efficacy according to the shot type, differentiating the moments of its application, under conditions of real practice. Two players were selected of deliberate form and in function of their characteristics. A quasi-experimental case design of type A-B-A was utilized. The trained specialist registered the data in real time individually and after, watching the games recorded, out agreed by consensus. For the statistical processing the t of Student test for independent measures was carried out, an averages meaning contrast test and an anova followed by the post hoc Tukey test. The application of the program allowed to improve the effectiveness in the shot interception for the types in real play situations and was maintained after the withdrawal of this program.  Key words: handball, goalkeeper, perception, training program